Alendronate prevents angiotensin II-induced collagen I production through geranylgeranylation-dependent RhoA/Rho kinase activation in cardiac fibroblasts - Yang Ye; Xue Lv; Mei-hui Wang; Jun Zhu; Shi-quan Chen; Chen-yang Jiang; Guo-sheng Fu (Elsevier, 2015)
Collagen I is the main component of extracellular matrix in cardiac fibrosis. Our previous studies have reported inhibition of farnesylpyrophosphate synthase prevents angiotensin II-induced cardiac fibrosis, while the exact molecular mechanism was still unclear. This paper was designed to investigate the effect of alendronate, a farnesylpyrophosphate synthase inhibitor, on regulating angiotensin II-induced collagen I expression in cultured cardiac fibroblasts and to explore the underlying mechanism. By measuring the mRNA and protein levels of collagen I, we found that alendronate prevented angiotensin II-induced collagen I production in a dose-dependent manner. The inhibitory effect on collagen I expression was reversed by geranylgeraniol, and mimicked by inhibitors of RhoA/Rho kinase pathway including C3 exoenzyme and GGTI-286. Thus we suggested geranylgeranylation-dependent RhoA/Rho kinase activation was involved in alendronate-mediated anti-collagen I synthetic effect. Furthermore, we accessed the activation status of RhoA in alendronate-, geranylgeraniol- and GGTI-286-treated cardiac fibroblasts and gave an indirect evidence for RhoA activation via geranylgeranylation. Then we came to the conclusion that in cardiac fibroblasts, alendronate could protect against angiotensin II-induced collagen I synthesis through inhibition of geranylgeranylation and inactivation of RhoA/Rho kinase signaling. Targeting geranylgeranylation and RhoA/Rho kinase signaling will hopefully serve as therapeutic strategies to reduce fibrosis in heart remodeling.